206 EXPLORING THE RELATIONSHIP BETWEEN LONELINESS, FRAILTY, AND HEALTHCARE UTILISATION IN IRELAND'S OLDER ADULTS DURING THE COVID-19 PANDEMIC. (18th November 2021) - Gyenes, M; Jones, C; Madigan, R; Grunner, M; Sheehan, O C
Abstract: Background: The COVID-19 pandemic has disproportionately affected older adults, both in morbidity and mortality 1 . The effects of the pandemic go beyond contracting the SARS-CoV-2 virus, leading to devastating consequences, particularly for individuals over the age of 60. In Ireland, isolation in older adults was exacerbated by cocooning measures and geographical limitations. The purpose of this study was to explore the relationship between loneliness, frailty, and the utilisation of health services in a sample of sexagenarians in Ireland. Methods: Adults aged 60–70 attending COVID-19 vaccine appointments at a Level 3 Hospital in Ireland (n = 75) were invited to participate in a 36-item questionnaire. Participants reported demographic information and questions regarding physical well-being, healthcare utilisation, lifestyle and behaviours, and impact of vaccination. The survey also included three validated questionnaires: PRISMA-7 for frailty, SARC-F for sarcopenia, and the UCLA 3-Item Loneliness Scale (UCLA-3ILS). Results: Of the 75 survey respondents, the mean age was 63.2. 72% (n = 54) identified as female. 28% (n = 21) reported that they had been cocooning during the past year. While 84% (n = 63) of respondents reported that they cancelled routine medical appointments during the pandemic, none reported avoiding attending hospital. Five respondents met the criteria for frailty and four were identified as probable sarcopenic. There was no significant difference (p = 0.64) in mean scores on the UCLA 3-ILS between frail and non-frail individuals. Persons identified as sarcopenic were more likely to have higher scores on the UCLA-3ILS (p = 0.0005). Conclusion: This research highlights the multifaceted relationship between frailty, loneliness, and healthcare utilisation among Irish adults ages 60–70 during the COVID-19 pandemic. Future research in program, policy, and intervention development for at-risk older adults, particularly those who are frail, sarcopenic, and/or lonely, can work to reduce associated negative outcomes. Reference: 1. Kang S-J and Jung, SI. (2020). Age-Related Morbidity and Mortality among Patients with COVID-19. Infect Chemother., 52(2): 154–164.